ANALISIS AKAD PADA JUAL BELI MEBEL DI DESA SUNGAI REGAS KECAMATAN SUNGAI KAKAP PERSPEKTIF KOMPILASI HUKUM EKONOMI SYARIAH - Iksan Iksan; Ardiansyah Ardiansyah; Nanda Himmatul Ulya (Al-Aqad, 2023)
The purpose of this study is to determine the practice of buying and selling furniture in Sungai Rengas Village, Sungai Kakap District, as well as the practice of buying and selling furniture from the perspective of the Compilation of Sharia Economic Law (KHES). This type of research is qualitative research, while the technique in data collection uses primary data, namely observation, interviews, and in the form of documentation. The analysis techniques that researchers use are the stages of data collection, data reduction, data presentation, and conclusions. While in the test stage the validity of the data using triangulation. The results of this study concluded that: 1) The practice of buying and selling furniture in Sungai Rengas Village, Sungai Kakap District involves furniture owners and consumers. In buying and selling this order follows the theoretical study of the istisna contract, namely the provisions of the goods ordered are clear in form, content, and information. The payment method is also by the istisna contract contained in KHES, namely, consumers can pay in advance, in the middle, or at the end of the furniture manufacturing process. 2) Regarding the practice of buying and selling in the Sungai Rengas Furniture store, the theory used is by KHES, namely that each party agrees when a contract occurs on the ordered goods and has been explained in articles 104, 105, 106, 107, 108 and these articles are implemented in practice in the field even though the seller has never known before about KHES.